Adjustment of speaker’s referential expressions to an addressee’s likely knowledge and link with theory of mind abilities - Achim, Amélie M.; Fossard, Marion; Couture, Sophie; Achim, André (Frontiers in Psychology, 2015)
To communicate cooperatively, speakers must determine what constitutes the common ground with their addressee and adapt their referential choices accordingly. Assessing another person’s knowledge requires a social cognition ability termed theory of mind. This study relies on a novel referential communication task requiring probabilistic inferences of the knowledge already held by an addressee prior to the study. Forty participants were asked to present ten movie characters and the addressee, who had the same characters in a random order, was asked to place them in order. Theory of mind and other aspects of social cognition were also assessed. Participants used more information when presenting likely unknown than likely known movie characters. They particularly increased their use of physical descriptors, which most often accompanied movie-related information. Interestingly, a significant relationship emerged between our theory of mind test and the increased amount of information given for the likely unknown characters. These results suggest that speakers use theory of mind to infer their addressee’s likely knowledge and accordingly adapt their referential expressions.